2019
DOI: 10.1152/ajplung.00175.2019
|View full text |Cite
|
Sign up to set email alerts
|

Loss of endothelial sulfatase-1 after experimental sepsis attenuates subsequent pulmonary inflammatory responses

Abstract: Sepsis patients are at increased risk for hospital-acquired pulmonary infections, potentially due to postseptic immunosuppression known as the compensatory anti-inflammatory response syndrome (CARS). CARS has been attributed to leukocyte dysfunction, with an unclear role for endothelial cells. The pulmonary circulation is lined by an endothelial glycocalyx, a heparan sulfate-rich layer essential to pulmonary homeostasis. Heparan sulfate degradation occurs early in sepsis, leading to lung injury. Endothelial sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The patterning of sulfation (and thus negative charge) along the heparan polysaccharide allows for specific electrostatic interactions with positively charged residues of proteins. Image courtesy: Oshima et al 85…”
Section: Shedding Of Endothelial Heparan Sulfate and Hspgs During Sepsismentioning
confidence: 99%
“…The patterning of sulfation (and thus negative charge) along the heparan polysaccharide allows for specific electrostatic interactions with positively charged residues of proteins. Image courtesy: Oshima et al 85…”
Section: Shedding Of Endothelial Heparan Sulfate and Hspgs During Sepsismentioning
confidence: 99%
“…Concerning the HS chain biosynthetic genes, none of these clustered in this group. Instead, Group III clustered genes involved in the control of HS levels and quality, including EXTL2 82,83 , HPSE 84-86 and SULF1 70,87-89 (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that HS of lung endothelial glycocalyx displayed higher 6-O-sulfation content after septic injury, which was due to a downregulation of Sulf-1. Interestingly, the post-septic loss of Sulf-1 was necessary for CARS to occur, as the administration of exogenous recombinant Sulf-1 intravenously reversed the immunosuppression phenotype (92). In the same context, Sulfs could also participate in the degradation of the basement membrane, along with Heparanase and proteases to facilitate leukocyte migration toward inflammatory sites.…”
Section: Discussion: Potential Roles Of the Sulfs During Inflammationmentioning
confidence: 99%